LANGUAGE POLITENESS OF STUDENTS AND TEACHERS: AN ETHNOGRAPHIC STUDY - Rika Ningsih; Endry Boeriswati; Liliana Muliastuti (English Education Department, 2020)
This research is based on the discovery of students and teachers at SMAN 01 Logas Tanah Darat, Kuantan Singingi, Riau, who spoke impolitely. As people working in the world of education, students and teachers must certainly pay attention to politeness in language. For this reason, this research needs to be conducted to see the extent of the politeness of students and teachers in communicating in the realm of education. Also, this study not only looked at the politeness of students and teachers but also want to see the factors causing the impoliteness of students and teachers in speaking. This research uses a qualitative approach with ethnographic methods. Sources of data in this study were students and teachers at SMAN 01 Logas Tanah Darat, Kuantan Singingi, Riau. The data in this study are the speech of students and teachers containing six maxim of politeness raised by Leech. The results of this study indicate that students and teachers at SMAN 01 Logas Tanah Darat, Kuantan Singingi Riau can already be categorized politely in speech. This can be seen from the 101 utterances found that only 38 utterances are categorized as impolite or violate the six maxims of the politeness principle stated by Leech.